Impact of Locus of Control and Relationship Quality on Counterproductive Work Behavior through Trust in Leader and Psychological Empowerment: An Empirical Study on Workers in Public Hospitals in Basra - AlAbrrow, Hadi; AlNoor, Alhamzah (Jordan Journal of Business Administration, 2017)
This study seeks to provide a practical and theoretical framework about "the direct impact of locus of control and relationship quality on counterproductive work behavior through trust in leader and psychological empowerment". The theoretical framework has been built according to the five variables of the study and in light of the development of the basic assumptions for this study. The study investigated the public health sector in the province of Basra, Iraq, where the study included a number of government hospitals. This framework was tested in the governmental health sector in Basrah on a number of hospitals. The questionnaire was used as a data collection method for this study and the sample size amounted to 285. The Path Analysis software (AMOS V20) was used to test the hypotheses of the study. The results showed a negative effect of both locus of control and relationship quality on counterproductive work behavior. Furthermore, the results showed an indirect negative effect of locus of control and relationship quality on counterproductive work behavior through the mediating variables trust in leader and psychological empowerment.